How can we help? Supporting students in distance tertiary education: An evaluative study - Rachel McCahon (Flexible Learning Association of New Zealand, 2012)
This article reports on a study which investigated the role of student support in the completion of a distance education programme at tertiary level. It aimed to identify crucial methods of support in distance education, related to the nature of the student body in a specific programme of study. It found that a wide range of support mechanisms were needed and valued. Tutor attributes such as availability and approachability were regarded as crucial, personal knowledge of students by tutors increased students' sense of identification with the programme and the likelihood of their completion, and the effectiveness of support systems could be enhanced by the creation of a feeling of intimacy within an institution.